PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN STUDENT ACTIVE LEARNING BERBANTUAN MEDIA VISUAL MATH PADA POKOK BAHASAN PELUANG KELAS XI IPA SMA NEGERI 2 PURWOKERTO TAHUN PELAJARAN 2013/2014 - Anggrahini Anggrahini; Mardiyana Mardiyana; Tri Atmojo Kusmayadi (Jurnal Pembelajaran Matematika, 2014)
Abstract. The aims of the research were: (1) to find a proper Mathematics-teaching learning-kit using Student Active Learning (SAL) with Media Visual Math on Probability, (2) to know which one resulting in better students' achievement, Student Active Learning (SAL) with visual math media or direct teaching in improving the students' achievement. This research was conducted in two stages. The first stage was developing and deciding teaching learning kit using Student Active Learning (SAL) with media visual math involved in the research and development. In this stage, information collecting, planning, developing, trying out the teaching learning kit, and treating teaching learning kit using Student Active Learning (SAL) with media visual math were done. The try out was held in three teaching learning processes. The second stage was testing the effectiveness of the teaching learning kit in quasi experimental research. The population was XI Science program students of  SMA N 2 Purwokerto in the first semester year of 2013/2014. The sample was split in 2 groups, they were experiment group and control group. The technique of data analysis used here was student’s t analysis. From the analysis, we find that: (1) teaching learning kit using Student Active Learning (SAL) with Media Visual Math was a valid device based on  validator’s scoring, activity observation, skill and response of students, so it can be applied in SMA Negeri 2 Purwokerto; (2) the students taught using SAL with visual math media had better mathematics achievement than students taught using direct teaching. Keywords: Teaching learning kit, Student Active Learning (SAL), Visual Math Media